Secondary Hemochromatosis due to Chronic Oral Iron Supplementation - Ronald Lands; Emmanuel Isang (Case Reports in Hematology)
Iron may accumulate in excess due to a mutation in the HFE gene that upregulates absorption or when it is ingested or infused at levels that exceed the body’s ability to clear it. Excess iron deposition in parenchymal tissue causes injury and ultimately organ dysfunction. Diabetes mellitus and hepatic cirrhosis due to pancreas and liver damage are just two examples of diseases that result from iron overload. Despite the rapid growth of information regarding iron metabolism and iron overload states, the most effective treatment is still serial phlebotomies. We present a patient who developed iron overload due to chronic ingestion of oral ferrous sulfate. This case illustrates the importance of querying geriatric patients regarding their use of nonprescription iron products without a medical indication.